INVESTOR’S DISPOSITION ERROR AND THE ROLE OF REGRET IN STOCK MARKET: AN EXPERIMENTAL EVIDENCE FROM INDONESIA - Pangeran, Perminas; Kumalaningrum, Maria Pampa (European Scientific Journal, ESJ, 2015)
This study examines experimentally, the role of emotions of regret on investors’ disposition error in investment decisions. This experimental study used full factorial design, 2 x 2 (2 decision outcomes: negative and positive; 2 types of action: inaction (hold stocks) and action (sell stocks)). A total of 70 participants were included in this study. The findings showed that investors experience more intense regret over the negative outcomes (real loss and missed gain) than the positive outcomes (missed loss and real gain). As expected, the results revealed that investors experience more regret over negative outcomes which stem from hold loser stock than from identical outcomes that results from sell stock.